Usability of basalt fibres in fibre reinforced cement composites - Girgin, Zehra Canan; Yildirim, Mehtap Tak (SPRINGER, 2016)
In the recent years, the basalt fibre (BF) reinforced polymer composites were introduced to retrofit the structural elements. However, on the contrary, the studies on the use of BF in concrete are very limited. This study addresses experimentally to find out the performance of BF as an alternative to glass fibres for the usability in fibre reinforced cement composites (e.g. fac, ade panels). BF have some advantages such as fire resistance and alkaline resistance higher than those of glass fibres. The research was especially carried out to achieve the variation of the flexural strength in the extreme conditions that only cement was used as binder material. The heatrain test was conducted to observe durability of BF as well. The experimental results indicated that the flexural strain capacity of BF is sensitive to stress accumulation due to the cement hydration products in the matrix-fibre interface. This sensitivity especially increased during heat-rain durability test, however any sign of chemical attack in the alkaline environment was not observed in SEM images.
Keywords: Basalt; Glass; Fibre; Cement composite; Bending test; Durability; CONCRETE; BEHAVIOR; ENERGY; Construction & Building Technology; Engineering; Materials Science